2011
DOI: 10.1097/ccm.0b013e318206d3df
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of sepsis after multiple trauma: An analysis of 29,829 patients from the Trauma Registry of the German Society for Trauma Surgery*

Abstract: The incidence of sepsis decreased significantly over the study period; however, in this decade the incidence remained unchanged. Although overall mortality from multiple trauma has declined significantly since 1993, there has been no significant decrease of mortality in the subgroup of septic trauma patients. Thus, sepsis has remained a challenging complication after trauma during the past 2 decades. Recognition of the identified risk factors may guide early diagnostic workup and help to reduce septic complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
130
4
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(149 citation statements)
references
References 41 publications
6
130
4
9
Order By: Relevance
“…The mortality rate of our study population was 4%, lower than mortality rates reported by most previous studies [1, 5,6,14,15,20,21,25,27,35,36,38]. This reduction of mortality might be explained by constant progresses in the early treatment of pelvic ring injuries, including immediate mechanical stabilization of the pelvic ring and improved bleeding control techniques, but also by progresses in intensive care medicine and emergency management of multiple traumas [17,46]. We found most patients died from head injuries, followed by pelvic injuries.…”
Section: Discussioncontrasting
confidence: 51%
“…The mortality rate of our study population was 4%, lower than mortality rates reported by most previous studies [1, 5,6,14,15,20,21,25,27,35,36,38]. This reduction of mortality might be explained by constant progresses in the early treatment of pelvic ring injuries, including immediate mechanical stabilization of the pelvic ring and improved bleeding control techniques, but also by progresses in intensive care medicine and emergency management of multiple traumas [17,46]. We found most patients died from head injuries, followed by pelvic injuries.…”
Section: Discussioncontrasting
confidence: 51%
“…The data was collected from a single center, and the population sample size was relatively small, both factors setting limits on the robustness of the research. Similar results have been reported in others studies [15][16][17], however Singh et al reported different findings. He used trauma and injury severity score (TRISS), a combination index based on revised trauma score (RTS), injury severity score (ISS) and patient's age to predict the outcome in trauma cases [18] and the performance of TS, ISS and TRISS as predictors of survival was evaluated using the misclassification rate, the information gain and the relative information gain.…”
supporting
confidence: 81%
“…Worldwide, in the general population under the age of 45, trauma is one of the main causes of death (Wafaisade et al, 2011). Although there are many immediate effects of trauma following the initial injury including cellular hypoxia and/or severe hypovolemic shock secondary to bleeding, traumatic injury leads to an immunologic deterioration in those individuals that survive.…”
Section: Introductionmentioning
confidence: 99%